Manajemen Pedagogik Guru dalam Mengembangkan Budaya Sekolah Berbasis Tatanen di Bale Atikan Sekolah Dasar - Aris Purwadin; Atik Kurniawati; Iin Sinta; Alwin Mujaiyanah; Nita Nurbaeti; Nisa Lutfi; Nana Herdiana; Revita Yanuarsari (Indra Institute Research & Publication, 2026)
This study aims to analyze teachers' pedagogical management in developing a school culture based on Tatanén di Balé Atikan (TdBA) in elementary schools in Purwakarta Regency. Using a qualitative approach with a case study method, data were collected through participatory observation, in-depth interviews with nine grade IV–VI teachers and three principals, and document analysis at three public elementary schools in Bungursari District that had implemented TdBA for at least two years. Thematic analysis revealed four dimensions of effective pedagogical management: (1) lesson planning that integrates TdBA values through the Pancaniti framework into subject-specific competencies; (2) implementation of project based learning in school gardens as